Growth performance of clarias gariepinus juveniles on cocoa pod husk-supplemented diets (2010)
An experiment was undertaken to determine the effect of boiling of cocoa pod husk and levels of inclusion that will positively affect the growth rate of Clarias gariepinus, a major species of importance cultured in Nigeria. Cocoa Pod husk is a by-product of cocoa industry often discarded as Waste. This study was to assess the effect of incorporation of boiled Cocoa pod husk into the diets of C .gariepinus juveniles. One hundred and thirty juvenile fish (3.35 g initial mean weight) were randomly allocated to five treatments each having two replicates. Two batches of cocoa pod husk were treated differently: the first batch was beaten to smaller pieces, sun dried and ground to fine powder, while the second batch was boiled for 30 minutes in water at100oC, sun dried and ground to fine powder. These were done in an attempt to reduce the anti nutritional factor, theobromine an alkaloid present in the CPH. The experimental diets consisted of 0% cocoa pod husk (control), 10% CPH (the best diet in a previous experiment), other treatment consisted of boiled cocoa pod husk at 10,15 and 20% levels of inclusion representing treatments 1 to 5 respectively. The experimental diets were formulated to contain 36% crude protein and fish were fed at 4% of their body weight thrice dally for 8 weeks. At the end of the trials the experimental diets were analyzed for their proximate composition, growth performance and nutrient utilization. From the result of the experiment, 10% of boiled CPH showed the best results (p<0.05) in terms of weight gain, protein efficiency ratio and feed intake of C. gariepinus juveniles. Therefore 10% inclusion of CPH was recommended for inclusion in diets of C. gariepinus juveniles. However further research should be carried out on other processing conditions of cocoa pod husk that will allow higher inclusion and efficient utilization by fish.